Analysis of Non-Performing Loans at PT Bank BRI Tbk (2019–2023) - Musadat, Irfan Achmad; Putra, Okta Eka; Kusumawardhani, Aninditha Putri (Operations Research: International Conference Series, 2025)
This study aims to analyze the Non-Performing Loan (NPL) ratio of PT Bank BRI Tbk during the 2019–2023 period by applying a descriptive approach combined with horizontal financial analysis. The research relies on secondary data obtained from the bank’s published financial statements on the Indonesia Stock Exchange (IDX). The analysis focuses on NPL as a key indicator of credit risk without exploring causal relationships among variables. The findings show that Bank BRI’s NPL ratio remained below the regulatory threshold of 5% set by Bank Indonesia, indicating that the bank was in a relatively stable condition. However, annual fluctuations highlight the importance of strengthening credit risk management, particularly in periods of economic uncertainty and aggressive credit expansion. The results emphasize that while the overall performance remains within a safe limit, proactive strategies are required to sustain long-term credit quality.